Remittance Income and Social Resilience among Migrant Households in Rural Bangladesh - Sikder, Mohammad Jalal Uddin (SpringerLink Bücher, 2017)
This book examines how migrant remittances contribute to household social resilience in rural Bangladesh. Using a mixed methods approach, the authors show that remittances play a crucial role in enhancing the life chances and economic livelihoods of rural households, and that remittance income enables households to overcome immediate pressures, adapt to economic and environmental change, build economic and cultural capital, and provide greater certainty in planning for the future. However, the book also reveals that the social and economic benefits of remittances are not experienced equally by all households. Rural village households endure a precarious existence and the potentially positive outcomes of remittances can easily be undermined by a range of external and household-specific factors leading to few, if any, benefits in terms of household social resilience